Integrated Medical Emergency Model: an interactive web-based database - Hameed, Shihab A.; Alam, A. H. M. Zahirul; Chek Nuh, Nur Hafizah; Salim, Nur Huda (2010)
Medical, healthcare and emergency systems in Malaysia are mostly separated and not fully computerized as well as lack of utilization of mobility and Multimedia facilities. Other drawbacks include: Difficulty in searching and viewing up to date records for patient, doctor, hospital, and drug, since many of such records are still kept in filing cabinet and there is no unified electronic medical record EMR used in all medical centers. This leads to difficult in communication, hard to manage and exchange patient data between various medical units. The fully computerizing and combining of such medical systems will lead o produce a Novel Integrated Medical Emergency Model (IMEM). IMEM is being divided into three main parts: The web based database, the intelligent agent, and the mobility. The database part will communicate and cooperate with both intelligent agent and mobility. This research paper focus mainly on developing an interactive web based database to serve this integrated model, where all hospitals, healthcare and emergency centers can view the patient record simultaneously, exchanging, managing and collaborate on sharing resources between medical units. A prototype for this work is build and sample of the results are shown in this paper.